SOCIOECONOMIC IMPORTANCE OF PLANTAIN CULTIVATION IN GHANA - B. M. Dzomeku; A. A. Dankyi; S.K. Darkey (Journal of Animal and Plant Sciences, 2011)
A study was conducted to assess the socioeconomic importance of plantain production in Ghana. Data were collected from 300 farmers selected randomly from 20 villages using structured questionnaires. In addition 156 plantain sellers at transit selling points and mini-markets were interviewed. Secondary data were collected from Statistics, Research and Information Department of the Ministry of Food and Agriculture (SRID-MoFA) and other sources. Information obtained included household characteristics and household access to resources. Data from the survey were analyzed using descriptive statistics. The results showed that the mean age of plantain farmers was 47 years. The mean size of plantain farm of the respondent was two acres (0.8ha). Plantain cultivation contributed more income to female farmers than the male farmers. Increased research and extension activities have introduced improved production technologies to farmers hence contributed to the enhanced livelihood. Farmers get increased output per unit area and that production has been increasing at a faster rate than the area cropped. Plantain production experiences seasonal glut between October and December. The marketing of plantain involves a large number of producers and a few wholesalers who distribute plantain to consumers on a large scale.  The market queens play a very significant role at the organized markets. Four main channels leading to the consumer were identified: producer > wholesaler > retailer; producer>retailer; wholesaler>agri-industry; and producer> agri-industry. The four main constraints to plantain production identified by the farmers were credit, weeds, diseases and labour in that order. The major marketing problems were low price for the produce and the buyers dictating the price.
Keywords: Musa; Plantain; Production; Socio-economics; Marketing